Perilaku fatik ( fatigue ) baja kekuatan tinggi aisi 4140 pada kondisi austempering - Yanto, Sugi (Universitas Muhammadiyah Metro, 2023)
AISI 4140 steel is low alloy steel that is widely used for machine components such as crankshafts, gears, piston rods in vehicles. These components experience cyclic loading during the initial and final operating conditions. Therefore, the plastic properties of steel are needed so that the plastic deformation that occurs in steel can increase its fatigue life. treatment is Austempering given to AISI 4140 steel, where austempering is a heat treatment that can be used to increase strength, toughness, plastic properties of steel, and produce bainite microstructure. The purpose of the study was to analyse the effect of austempering on low cycle fatigue values and changes in microstructure. Tensile tests (ASTM E8) and Hight cycle fatigue (ASTM E606) were carried out with samples of AISI 4140 Steel which were given treatment austempering with a holding time of 60 minutes, and the variation of the stress level start 40%,45%,50%,55%, 60%,and 65% .The effect of austempering on the tensile test results showed an increase in tensile strength compared to the AISI 4140 Steel sample without treatment, austempering namely the yield stress increased by 22.59%, the stress ultimate increased by 12,45% as well as the plastic energy value of 19,83%. Microstructural observation through a microscope and using 3% nital etching resulted in a bainite microstructure which directly affects the increase in fatigue life and tensile strength of AISI 4140 steel.